Free space optical communication systems exploring advanced modulation formats - Carmo, Rui (My University, 2017)
In the near future, one of the solutions for the exponential increase in bandwidth requirements and transmission capacity will be the transition of wireless communications to its fifth generation (5G), which will represent an important step in the fast-paced evolution of telecommunications. In this context, the use of free-space optical links will undoubtedly be a valuable asset for improving the coverage, capacity and overall quality of experience in the datacenters and in urban centers as it is a flexible and low-cost solution. It is possible to propose optical backhaul solutions with high capacity, spectral and energy efficiency, but also with low cost per bit. Thus, the present work proposes the study of advanced modulation formats, with potentiality of application in optical communication systems in free-space, favoring the possibility of using direct detection. In this sense, a project will be carried out, consisting on the implementation of a low-cost point-to-point optical communications module, operating in the visible spectral region and based on the direct modulation of the optical emitter. By modulating a subcarrier, the BPSK and QPSK formats are used, thus allowing increased spectral efficiency of the connection. From QPSK modulation, it was able to achieve an EVM(%) of 1.3%.
Sistemas de Comunicações Óticas em Espaço Livre Explorando Formatos de Modulação Avançados
Aspirante a Oficial-Aluno ENGEL 137737-L. Estabelecimentos de Ensino Superior: IST/AFA
Keywords: Free-space optical communications; Advanced modulation formats; Phase modulation; Subcarrier modulation; Direct detection; Comunicações óticas em espaço livre; Formatos de modulação avançados; Modulação da subportadora; Modulação de fase; Deteção direta